Legal Clarity for Sharia Lodging Businesses through Sharia Certification - Rasmuddin, Rasmuddin; Umar, Wahyudi; Sudirman, Sudirman; Rustan, Ahmad; Lambooy, Tineke (Jurnal Media Hukum, 2024)
The development of the Sharia business in Indonesia has become the most potential business not only in Islamic banking but also the non-Islamic bank financial industries, such as Islamic insurance, Islamic pension funds, Islamic finance companies, Islamic bonds (sukuk), Islamic mutual funds, and even Islamic lodging. This phenomenon makes the Sharia "label" as a trend. This research aims to analyze the urgency of Sharia certification in the Sharia lodging business in Indonesia. The method used is a type of normative legal research with statutory approaches, case approaches, and conceptual approaches. The results of this study indicate that the urgency of Sharia certification in the Sharia lodging business is to maintain the image of Islamic teachings and to provide certainty to consumers. This is because the application of Sharia in business institutions bearing the Sharia label still shows that the concept of Sharia understood by these business institutions still seems partial/not kaffah (total). Besides that, the Sharia "label" in the lodging business is used mostly as a brand or company brand. Therefore, it is high time for Sharia lodging certification to be carried out, like the halal label certificate on food products